DEVELOPMENT OF HISTORY VIRTUAL CLASS BY APPLYING COLLABORATIVE MODEL TO IMPROVE CRITICAL THINKING ABILITY - Suryani, Nunuk (History Department, Semarang State University and Historian Society of Indonesia, 2014)
The efforts to improve quality of history learning and to answer the global demand can be carried out by utilizing technology. One of them is by developing the virtual class in history learning. These research and development are intended to produce a collaborative model of history virtual class in order to improve the critical thinking ability on the history values at the students of Senior High School. The research is conducted at a Senior High School in Solo Raya in the year 2014. This research is designed to apply the development research pursuant to the opinion of Borg and Gall. The data are collected by using the techniques of observation, interview, document analysis, FGD (Focus Group Discussion) and questionnaire. The methods applied to analyze the data are the qualitative analysis using interactive model, evaluative and comparatives analyses. The finding of this research produces a conclusion that the model of history virtual class is effective to improve the critical thinking ability on the history values. The collaborative model of virtual class is effective to improve the role of history learning in stimulating the critical thinking ability of the students which in turn will be able to improve competence of the students.Key words: History Virtual Class, Critical Thinking Ability, Collaborative Model.Upaya untuk meningkatkan kualitas pembelajaran sejarah dan untuk menjawab permintaan global dapat dilakukan dengan memanfaatkan teknologi. Salah satunya adalah dengan mengembangkan kelas virtual dalam sejarah pembelajaran. Penelitian dan pengembangan ini dimaksudkan untuk menghasilkan model kolaboratif sejarah kelas virtual untuk meningkatkan kemampuan berpikir kritis pada nilai-nilai sejarah di siswa SMA. Penelitian dilakukan di SMA Senior di Solo Raya pada tahun 2014. Penelitian ini dirancang untuk menerapkan penelitian pengembangan sesuai dengan pendapat Borg dan Gall. Data dikumpulkan dengan menggunakan teknik observasi, wawancara, analisis dokumen, FGD (Focus Group Discussion) dan kuesioner. Metode yang diterapkan untuk menganalisis data adalah analisis kualitatif dengan model interaktif, evaluatif dan analisis komparatif. Temuan penelitian ini menghasilkan kesimpulan bahwa model sejarah kelas virtual yang efektif untuk meningkatkan kemampuan berpikir kritis pada nilai-nilai sejarah. Model kolaboratif kelas virtual adalah efektif untuk meningkatkan peran sejarah pembelajaran dalam merangsang kemampuan berpikir kritis siswa yang pada gilirannya akan dapat meningkatkan kompetensi siswa.Kata kunci: kelas virtual sejarah, kemampuan berpikir kritis, model kolaboratif